KNOWLEDGE OF PERFORMANCE AS AN INCENTIVE IN REPETITIVE, MONOTONOUS TASKS. - Chapanis, Alphonse (Journal of Applied Psychology)
This experiment tried to isolate the purely motivational effect of knowledge of performance from its informational and rewarding aspects. The subjects (Ss) worked an hour a day, for 24 days, punching random digits into a teletype tape. They were told they were programming a computer and efforts were made to lend credibility to this fiction. 16 male undergraduate students were assigned to 1 of 4 groups. Ss in 1 group received no information about their output. In 2 other groups, the Ss could see a counter which tallied every stroke on the perforator and could, if they so chose, determine their daily work output. In the 4th group Ss were required to write down their output at the end of 15, 30, and 45 minutes, "for accounting purposes only." No significant differences were discovered among the 4 groups. Suggestions are offered to account for the discrepancy between the results of this experiment and those of a similar experiment reported by Gibbs and Brown in 1955.